Analisis Manajemen Resiko Bisnis: - Ahmad Fauzi; Andri Wibowo; Asyaadatun Nazila Selayan; Sakinah Jahrani Nst (VISA: Journal of Vision and Ideas, 2022)
Small, Medium establishments or typically referred to as SME are also needed to guard themselves in competition, besides SME are also required to stand a few global demanding situations, in going through international demanding situations this will be performed by way of innovating products and services, and growing human sources and generation, also are wanted in terms of growing advertising regions. for that reason, hazard control is needed to count on or lessen the likelihood of these risks via studying risk management. Keywords: business risk management, sme,